x = 1/3
y = 2/3
Subtract eq.2 from eq.1
4x + 1y = 2 (eq.1)
- 1x + 1y = 1 (eq.2)
-----------------
3x + 0 = 1
:: x = 1/3
Substitute 1/3 into X to solve for Y in eq.2
1(1/3) + 1y = 1
1/3 + 1y = 1
Subtract 1/3 from both sides:
y = 1 - 1/3
y = 2/3
Check the answer, substitute 1/3 for x and 2/3 for y into eq.1
4(1/3) + 2/3 = 2
4/3 + 2/3 = 2
6/3 = 2
2 = 2
Check the answer, substitute 1/3 for x and 2/3 for y into eq.2
1/3 + 2/3 = 1
2007-01-11 12:52:51
·
answer #1
·
answered by ♫ Life is a Highway ♫ 4
·
0⤊
0⤋
x + y = 1 -->X = -y + 1
y + 4x = 2 ->y + 4x = 2
y + 4(-y + 1) = 2
[distribute 4]
y + -4y + 4 = 2
[subtract 4 from both sides]
[add "y"s together]
-3y = -2
[divide -3 from both sides]
y = 2/3 <----with this you can now solve "x"; just plug it in the given equation (x + y = 1) and u'll get (1/3)...when you check your answer: x+ y = 1 is the same as 1/3 + 2/3 = 1)
get it?? okay. =)
2007-01-11 20:54:34
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
x + y = 1 or y+x=1
y + 4x = 2
y+x=1 subtract
3x=1
x=1/3
1/3+y=1
y=2/3
check 2/3+4/3=2
6/3=2
2=2
(1/3, 2/3)
2007-01-11 20:49:44
·
answer #3
·
answered by yupchagee 7
·
0⤊
0⤋
if x+y=1, then y=1-x, so plug that into your other equation
(1-x)+4x=2
3x+1=2
3x=1
x=1/3
then plug x=1/3 into the 1st equation
(1/3)+y=1
y=2/3
2007-01-11 20:54:59
·
answer #4
·
answered by Megan07 1
·
0⤊
0⤋
3x = 1
x=1/3
y = 2/3
2007-01-11 20:48:02
·
answer #5
·
answered by BigPappa 5
·
0⤊
0⤋
y=1-x
x=1-y
and
y=2-4x
x=(2-y)/4
2007-01-11 20:49:35
·
answer #6
·
answered by tomkat1528 5
·
0⤊
0⤋
I hate math so much. It takes too much time lol
2007-01-11 20:52:56
·
answer #7
·
answered by Belle 2
·
0⤊
0⤋